1983
DOI: 10.1111/j.1471-0528.1983.tb09302.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled study comparing vaginal prostaglandin E2 pessaries with intravenous oxytocin for the stimulation of labour after spontaneous rupture of the membranes

Abstract: Summary. In a prospective randomized study, 36 patients with spontaneous rupture of the membranes of ≥4 h duration were stimulated with 3 mg vaginal prostaglandin E2 pessaries or intravenous oxytocin. Oxytocin stimulation was associated with shorter labours and a lower incidence of abnormal cervimetric progress. Of the patients given prostaglandin pessaries, 40% required a second dose after 4 h for slow progress; 45% of the primigravidae subsequently developed abnormal labour which was corrected by augmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Several studies compared the effectiveness of vaginal prostaglandin with intravenous oxytocin for induction of labor after spontaneous rupture of the membranes, but their results are conflicting. Magos et al 14 and Lange et al 15 found oxytocin more efficient in stimulating labor, whereas Mahmood et al 16 and Ray and Garite 17 claim that vaginal prostaglandins administration is superior.…”
mentioning
confidence: 99%
“…Several studies compared the effectiveness of vaginal prostaglandin with intravenous oxytocin for induction of labor after spontaneous rupture of the membranes, but their results are conflicting. Magos et al 14 and Lange et al 15 found oxytocin more efficient in stimulating labor, whereas Mahmood et al 16 and Ray and Garite 17 claim that vaginal prostaglandins administration is superior.…”
mentioning
confidence: 99%
“…Some studies have been criticized for not being fully randomized trials (Duff et al 1984; Morales & Lazar 1986) and the three studies by (Hauth et al (1977); Lange et al (1981) and Magos et al (1983) for not including a third study arm dealing with conservative management. We designed a prospective study to test the hypothesis that treatment with prostaglandin (PG) E 2 gel would halve the PROM to delivery interval without increasing the frequency of caesarean section or of infective morbidity.…”
mentioning
confidence: 99%
“…This section rate can vary from 3 to 47% with many variables accounting for this inconsistency. Some studies have been based on very small numbers (Magos, et al . 1983; Ekman‐Ordeberg, et al .…”
mentioning
confidence: 99%
“…1979) seemed to be associated with very early recourse to section. Some authors started oxytocin within 4–6 h (Magos et al . 1983, Lange et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation